1999
DOI: 10.1042/cs0970585
|View full text |Cite
|
Sign up to set email alerts
|

Use of opposing reflex stimuli and heart rate variability to examine the effects of lipophilic and hydrophilic β-blockers on human cardiac vagal control

Abstract: Evidence from animal studies suggests that beta-blockers can act within the central nervous system to increase cardiac vagal motoneuron activity. We have attempted to determine whether such an effect is evident in healthy humans, by examining the effects of lipophilic and hydrophilic agents on heart rate variability and cardiac vagal reflexes. A total of 20 healthy volunteers took part in the study. Autonomic studies were performed after 72 h of treatment with placebo, atenolol or metoprolol in a blinded cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…However, in another study lipophilic and hydrophilic ␤-blockers had similar effects on responses to cardiovascular reflex testing and heart rate variability. 10 This finding is not consistent with an important effect of central ␤-adrenoreceptors on autonomic regulation because lipophilic agents cross the blood-brain barrier, whereas hydrophilic ␤-blockers mainly act in peripheral tissues. We tested the hypothesis that central nervous ␤-adrenoreceptors have a tonic stimulatory effect on the sympathetic nervous system and that this effect can be attenuated by systemic ␤-blockade.…”
mentioning
confidence: 87%
“…However, in another study lipophilic and hydrophilic ␤-blockers had similar effects on responses to cardiovascular reflex testing and heart rate variability. 10 This finding is not consistent with an important effect of central ␤-adrenoreceptors on autonomic regulation because lipophilic agents cross the blood-brain barrier, whereas hydrophilic ␤-blockers mainly act in peripheral tissues. We tested the hypothesis that central nervous ␤-adrenoreceptors have a tonic stimulatory effect on the sympathetic nervous system and that this effect can be attenuated by systemic ␤-blockade.…”
mentioning
confidence: 87%
“…In that context, it is unlikely that the use of beta-blockers has influenced only the results obtained with the HRV. There is consistent evidence that beta-blockers increase CVM through both a direct effect on the central nervous system 3 and a peripheral effect, due to a reduction in heart rate, which increases the probability that acetylcholine acts on the slow diastolic depolarization of sinoatrial node cells 4 , and due to a reduction in the pre-synaptic inhibition of the release of acetylcholine mediated by sympathetic activity 5 .…”
Section: Santos Et Al Comparison Of Vagal Assessment Methodsmentioning
confidence: 97%
“…; B) the use of beta-blockers was observed in 100% of the patients with coronary heart disease, as expected, considering the current guidelines, and in 0% of the healthy group. Autonomic modulation depends on a complex regulatory mechanism involving interaction between the sympathetic and parasympathetic pathways 3,4 . However, after beta-blockade, the "modulatory" behavior of the vagus nerve is no longer spontaneous.…”
mentioning
confidence: 99%
“…It has been suggested that a rate-independent effect of a drug on heart rate variability can be established by demonstrating an effect on heart rate variability normalized for the heart rate (eg, expressing the standard deviation of the R-R intervals as a percent of the mean R-R interval, ie, its coefficient of variation). 86 Such correc-tions have not yet been clearly reported in the setting of omega-3 FA, and further research is warranted.…”
Section: Clues To the Occurrence Of Antiarrhythmic Effects Of Omega-3mentioning
confidence: 98%
“…[82][83][84][85][86] In a highly consistent series of studies, Christensen et al have shown an effect of omega-3 FA on heart rate variability in humans. First, in 55 postmyocardial infarction patients with left ventricular dysfunction, these authors documented a direct relationship between habits of fish consumption (and corresponding omega-3 FA levels in platelet membranes) and heart rate variability, expressed as the standard deviation of the R-R interval on 24-hour Holter monitoring.…”
Section: Clues To the Occurrence Of Antiarrhythmic Effects Of Omega-3mentioning
confidence: 99%